Social media law and ethics - Lipschultz, Jeremy Harris, 1958- (Routledge, 2022)
"In this new textbook, social media professor Jeremy Lipschultz introduces students to the study of social media law and ethics, integrating legal concepts and ethical theories. The book explores free expression, as it applies to students, media industry professionals, content creators and audience members. Key issues and practices covered include copyright law, data privacy, revenge porn, defamation, government censorship, social media platform rules, and employer policies. Research techniques are also used to suggest future trends in social media law and ethics. Touching on themes and topics of significant contemporary relevance, this accessible textbook can be used in stand-alone law and ethics courses, as well as emerging social media courses that are disrupting traditional public relations, advertising and journalism curricula. Case studies, discussion questions, and online resources help students engage with the complexities and ambiguities of this future-oriented area of media law, making it an ideal textbook for students of media law, policy and ethics, mass media, and communication studies"--